The Role of Job Satisfaction Mediation and Employee Engagement on the Influence of Work-Life Balance on Employee Performance in Information Technology Companies - Putra, Rizky Narendra; Rachmawati, Riani (Dinasti Publisher, 2025)
The swift growth of Information Technology (IT) enterprises across Jakarta's region creates a major obstacle: maintaining work-life balance for staff members while facing demanding productivity pressures and unpredictable work schedules, both factors contributing to elevated stress levels. This research sought to examine how work-life balance affects employee performance, with particular focus on investigating the mediating functions of job satisfaction and employee engagement within IT company workforces. Through a quantitative methodology, information was gathered from 195 full-time employees using digital questionnaires and examined with SmartPLS 4.0 software. The results demonstrate that proper work-life balance creates positive effects on employee performance, especially when mediated significantly by employee engagement. Conversely, job satisfaction failed to appear as a meaningful mediator within this connection. To summarize, for enhancing employee performance, IT enterprises must emphasize work-life balance strategies that proactively encourage employee engagement. This method has demonstrated superior effectiveness compared to concentrating exclusively on job satisfaction alone.